Reflecting on Alister McGrath’s Love for Science and Discovery of God: Learnings for Non-Christian Theists - Blessing T. Adewuyi (Religions, 2025)
Oxford’s Alister McGrath undoubtedly reflects a paradigm of meaningful intersection in the scholarship of science and religion, especially Christian theology. McGrath’s life journey from loving science to discovering God in Christianity is particularly intriguing because his convictions were not supernatural but intellectual, rooted in multiple conscientious inquiries culminating in his conclusion that through Christianity, humanity and creation can be better understood. A recurring quote in McGrath’s writings comes from C.S Lewis: “I believe in Christianity as I believe that the sun has risen not only because I see it, but because by it I see everything else”. How do spiritual eclipses influence religious belief? What might non-Christian theistic religion like African traditional perspectives glean from a uniquely Christian outlook? This paper, leveraging McGrath’s unique journey as a bridge between religion and science, unravels intelligible parallels between two different religious perspectives and learnings that non-Christian theists can glean from exclusively Christian scholarship.